Thermo-mechanical characterization of a silica-alumina refractory concrete based on calcined algerian kaolin. Issue 8 (June 2016) - Benali, F.; Hamidouche, M.; Belhouchet, H.; Bouaouadja, N.; Fantozzi, G.
Abstract: The aim of this work is to study the thermo-mechanical behaviour (bending and compressive tests, creep and thermal shock resistance) of a refractory concrete based on local kaolin grogs and aluminous cement. Strength tests revealed a behaviour that is almost linear elastic for temperatures up to 800 °C and visco-plastic at 900 °C. A crack bridging strengthening process was observed at 800 °C. The creep tests were carried out at different temperatures between 1000 and 1150 °C using stresses in the range (0.75–2.76 MPa). The stress exponent was about 1.255. Microscopic observations suggested an intergranular creep mechanism. A water quenching test was used for estimating the thermal shock resistance of the material. The tested samples supported 80 cycles of standardized cyclic thermal shock without failure. Ultrasonic measurements were applied in order to evaluate the of ultrasonic velocity changes after these thermal shock tests. Strength degradation of the samples was evaluated using two models based on ultrasonic velocity changes during test and compared with the experimental values.